2011
DOI: 10.1016/j.ica.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

New chelate complexes of trivalent Y and lanthanides (Eu, Ho, Yb) with a triazene N-oxide: Synthesis, structural characterization and luminescence properties

Abstract: Deprotonated 3-(4-nitrophenyl)-1-phenyltriazene N-oxide reacts with YCl 3 Á6H 2 O and LnCl 3 Á6H 2 O (Ln = Eu, Ho, Yb) to give the monoclinic chelate complexes [Y{O 2 N(C 6 H 4)NNN(O)Ph} 4 ](Et 3 NH)ÁH 2 O (1) (Ph = C 6 H 5 ; Et = C 2 H 5) and [Ln III {O 2 N(C 6 H 4)NNN(O)Ph} 4 ](Et 3 NH)ÁH 2 OÁ{CH 3 OH * } {Ln III = Eu (2), Ho (3), Yb * (4), in which the metal centers present a square antiprismatic configuration. As already observed for hydrated ammonium complexes of triazene-oxides ligands with (C 6 H 4)ÀNO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In triazenes, the presence of electron-withdrawing groups in the ortho and para positions of the aryl groups can also influence the tautomerism. However, in our study, the only product we could obtain in acceptable purity was the depicted compound (1) to (4). In addition to different factors, the formation of a 6-membered ring via the intramolecular hydrogen bonding is also responsible for stabilization of this tautomer.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In triazenes, the presence of electron-withdrawing groups in the ortho and para positions of the aryl groups can also influence the tautomerism. However, in our study, the only product we could obtain in acceptable purity was the depicted compound (1) to (4). In addition to different factors, the formation of a 6-membered ring via the intramolecular hydrogen bonding is also responsible for stabilization of this tautomer.…”
Section: Resultsmentioning
confidence: 69%
“…Cell constants and orientation matrices for data collection were obtained by least-squares refinement of diffraction data from 2904 unique reflections for (3), 2690 for (4) and 2717 for compound (6). Data were collected to a maximum 2h value of 29.1°for (3) and 29.2°for (4) and (6), in a series of x scans in 1°oscillations and integrated using the Stoe X-AREA [32] software package. A numerical absorption correction was applied using X-RED [33] and X-SHAPE [34] software.…”
Section: Crystal Structure Determination and Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, triazenes have been received much attention due to their novel physical and chemical properties, and prospects of their application in the synthesis of photosensitive polymers,1–5 13 N‐labeled azo compounds,6 conductive polymer,7 and hybrid nanocomposites are used for detecting metal ions 8. Moreover, they have been applied as coordination agents in inorganic chemistry,9, 10 triazene linkers,11–15 photolabile linker in solid‐phase chemistry,16 solid‐phase extraction,17 thiophenol synthesis,18 and improvement in semiconductor laser printing 19. Hence, triazene‐group‐containing polymers can be potentially interesting due to the possibilities of its applications such as each of the above uses.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, the vibrational levels of the O-H bonds of the water lead to the quenching of the luminescence -in the case of luminescent lanthanides ions -by absorption of the emitted radiation in the vibrational excitation processes [1]. In addition, we have already shown that some polydentate nitrogen ligands are able to transfer energy to a lanthanide ion, thus exciting its luminescence -the so-called ''antenna'' effect [2][3][4]. Although relatively recent, the chemistry of lanthanides and actinides ions with ligands derived from 2,6-diformylpyridine and 2,6-diacetylpyridine is fairly reach and interesting.…”
Section: Introductionmentioning
confidence: 99%